2021
DOI: 10.1007/s40831-021-00340-8
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Zn as ZnO from Steelmaking Waste Materials by Mechanochemical Leaching, Solvent Extraction, Precipitation, and Thermal Decomposition Route

Abstract: A large amount of electric arc furnace dust (EAFD) is produced as hazardous waste materials during steelmaking in electric arc furnace. EAFD includes a considerable amount of zinc. Recovery of Zn as ZnO from EAFD via mechanochemical leaching, solvent extraction, precipitation, and thermal decomposition route was investigated. Dissolution behavior of Zn, Fe, Mn, Si, Mg, and Ca during the mechanochemical leaching of EAFD in H 2 SO 4 solution was determined. Optimum mechanochemical leaching parameters were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…To determine the most effective ionic liquid and oxidant combination for the extraction of Zn, In, and Ga from EAFD, two imidazolium-based ionic liquids, [Bmim + HSO 4 − ] and [Bmim + Cl − ] (50 mL, 50% v / v ), were mixed with one of three selected oxidants, KMnO 4 (0.5 g), Fe 2 (SO 4 ) 3 (0.5 g), or 50% H 2 O 2 (1 mL) ( Figure 4 ). After conducting the experiments, it was found that [Bmim + HSO 4 − ] performed considerably better than [Bmim + Cl − ] due to the ability of [Bmim + HSO 4 − ] to act as a Brønsted acid, which allows the anionic species [HSO 4 − ] to release the associated proton [H + ] into the solution [ 16 , 17 , 18 ]. Furthermore, the sulphate [SO 4 2− ] is able to act as a better ligand (compared to Cl − ) to form a stable complex with the target metals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine the most effective ionic liquid and oxidant combination for the extraction of Zn, In, and Ga from EAFD, two imidazolium-based ionic liquids, [Bmim + HSO 4 − ] and [Bmim + Cl − ] (50 mL, 50% v / v ), were mixed with one of three selected oxidants, KMnO 4 (0.5 g), Fe 2 (SO 4 ) 3 (0.5 g), or 50% H 2 O 2 (1 mL) ( Figure 4 ). After conducting the experiments, it was found that [Bmim + HSO 4 − ] performed considerably better than [Bmim + Cl − ] due to the ability of [Bmim + HSO 4 − ] to act as a Brønsted acid, which allows the anionic species [HSO 4 − ] to release the associated proton [H + ] into the solution [ 16 , 17 , 18 ]. Furthermore, the sulphate [SO 4 2− ] is able to act as a better ligand (compared to Cl − ) to form a stable complex with the target metals.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one of the main characteristics of [Bmim + HSO 4 − ] is its ability to substantially lower the leaching solution’s pH, making the solution acidic [ 16 , 17 ]. For instance, it was found that for 50% v / v [Bmim + HSO 4 − ], the pH was ~0.88, whereas for the equivalent 50% v / v [Bmim + Cl − ], the leaching solution’s pH was ~4.7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations